PILIHAN KARIR DAN ISU GENDER AKTIVIS WANITA PADA LEMBAGA SWADAYA MASYARAKAT DI SURABAYA DAN SEKITARNYA - Muazaroh ,; Emma Yulianti (Media Riset Bisnis & Manajemen, 2009)
This research attempts to discover the reasons of the women who are interested in working in the non government organization and reveal their aspiration to be involved in such an organization. Besides that, it also attempts to understand the women's freedom in determining their careers and the variables influencing such a determination. It includes twenty woman activists in the non government organization. Based on the in-depth interview with the woman activists working in the non government organization, the reasons of being interested in working in such organization such as their concern of social environment, seeking an experience and place for learning, expressing their idealism, being flexible to manage time and independent or without depending on others. Furthermore, the determination of this career as woman activists in the non government organization is not due to being forced. Keywords: NGO, Motivation, Career, Aspiration